A study of gas permeation on a polymeric membrane: permeability, diffusivity, solubility, and its performance for H2/CO2 separation - FACHRUL RAZI (LPPM Universitas Malikussaleh, 2017)
The gas permeation on a polymeric membrane for H2/CO2 separation in accordance to the solution-diffusion mechanism was studied. A commercial Polyvinyl alcohol (PVA) and Polyamide (nylon-6) membrane were used for pure and mixed gas permeation experiment and the interaction effects of the permeance gas with these polymeric membranes were observed by determining transports parameter such as permeability coefficient (P), diffusion coefficient (D), and solubility coefficient (S). Two-steps experiments were carried out:(1) pure gas permeation of H2 and CO2, and (2) mixed gas permeation of H2-CO2 (30 % H2 - 70 %-v CO2). The operating pressure was varied in the range from 4 to 12 bars. Membrane performance on a gas separation was represented by permeation flux (J) and its selectivity factor (α). The experiment result showed that solubility of CO2 in PVA was greater than Nylon-6 membrane and decrease with an increasing operating pressure. Permeability and permeation flux of H2 were higher at both two types of membrane while the selectivity of H2/CO2 of nylon-6 membrane was higher in compared to PVA membrane.